2021
DOI: 10.3390/cells10020315
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Mitochondrial Transcription Termination Factor mTERF2 Promotes Splicing of Group IIB Introns

Abstract: Plastid gene expression (PGE) is essential for chloroplast biogenesis and function and, hence, for plant development. However, many aspects of PGE remain obscure due to the complexity of the process. A hallmark of nuclear-organellar coordination of gene expression is the emergence of nucleus-encoded protein families, including nucleic-acid binding proteins, during the evolution of the green plant lineage. One of these is the mitochondrial transcription termination factor (mTERF) family, the members of which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…In this study, 14 genes with positive selection sites are identified in four genera of Globba , Hedychium , Kaempferia and Zingiber in subfamily Zingiberoideae. Among these genes containing amino acid positive sites, three genes of them encoding ribosome subunit proteins ( rpl20 , rps12 and rps18 ), are involved in chloroplast gene expression, which is essential for chloroplast biogenesis and function [ 52 ]. rps12 gene exhibits its variations in intragenic exon location and intron content, and has important effects on evolutionary rates and patterns of molecular evolution in fern [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 14 genes with positive selection sites are identified in four genera of Globba , Hedychium , Kaempferia and Zingiber in subfamily Zingiberoideae. Among these genes containing amino acid positive sites, three genes of them encoding ribosome subunit proteins ( rpl20 , rps12 and rps18 ), are involved in chloroplast gene expression, which is essential for chloroplast biogenesis and function [ 52 ]. rps12 gene exhibits its variations in intragenic exon location and intron content, and has important effects on evolutionary rates and patterns of molecular evolution in fern [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…rps12 gene exhibits its variations in intragenic exon location and intron content, and has important effects on evolutionary rates and patterns of molecular evolution in fern [ 53 ]. Its spicing activity has been reported to impair photosynthesis and perturb development in Arabidopsis [ 52 ]. In our analyses, rps12 gene harbors the highest number (40) of positive amino acid sites within 17 Zingiberoideae species, suggesting that the rps12 gene may play important roles in Zingiberoideae species evolution and development.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study reported that mTERF2 is implicated in the splicing of the group IIB introns of ycf3 (intron 1) and rps12 in Arabidopsis. Knock-down mTERF2 resulted in delayed flowering time and knock-out mTERF2 mutants were embryo lethal (Lee et al, 2021). In maize, ZmmTERF4 is involved in plastid ribosome accumulation and promote group II intron splicing of trnI.2, trnA, rpl2, atpF, and ycf3-2 in chloroplasts (Hammani and Barkan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To identify the targets of RBP45D, RNA immunoprecipitation experiments were performed on rls6 mutants complemented by expression of Myc-tagged RPB45D (see Figure S1B). Libraries prepared from RNAs that co-immunoprecipitated with RBP45D-Myc [and another unrelated protein-Myc fusion (Lee et al, 2021) as a control] were subjected to RNA sequencing (RIP-Seq). Based on the functions of its orthologs in other organisms, RBP45D has been suggested to be a component of the U1 snRNP (Kanno et al, 2020).…”
Section: Rbp45d Is a Nuclear Protein That Binds To Snrnas And Snornasmentioning
confidence: 99%